Observations on the feeding preference of the phytoseiid predator, Neoseiulus longispinosus (Evans) on the different life stages of the spider mite, Oligonychu sbiharensis (Hirst). Issue 6 (17th August 2020) - Devasia, Jyothis; Ramani, N.
ABSTRACT: A comparative evaluation of feeding preference of the phytoseiid predator, Neoseiulus longispinosus (Evans) was made on the different life stages of spider mite Oligonychus biharensis (Hirst) under laboratory conditions by raising stock cultures of pest mite on leaves of its native host, Bauhinia purpurea . N.longispinosus collected from field was reared on mixed prey stages of O. biharensis. Feeding experiment was conducted following leaf disc method and known numbers of various prey life stages egg, larva, nymphs, and females (pre-oviposition period) were offered simultaneously to the nymph and adult female of N.longispinosus . Number of prey stages consumed by the predator after 24 hours and consumption percentage were recorded. Feeding preference of adult predator towards prey stages decreased as follows: nymph (14.1%)> larva (13.3%)> egg (10.4%) > adult (2.2%). Predator nymph exhibited a similar order of preference with respective consumption rates of 13.3%, 13.3%, 7.5%, and 0% on the egg, larva, nymph, and adult female, respectively. Statistical analysis following ANOVA revealed a significant variation (p < 0.05) in feeding preference of the predator life stages towards varied life stages of the prey mite. Thus, results of the study clearly revealed the bio-control potential of N.longispinosus against the pest mite O. biharensis.